2009
DOI: 10.1136/ard.2008.093088
|View full text |Cite
|
Sign up to set email alerts
|

The influence of socioeconomic status on the reporting of regional and widespread musculoskeletal pain: results from the 1958 British Birth Cohort Study

Abstract: These results emphasise the importance and potential impact of measures to reduce social adversity, which will have the effect of improving musculoskeletal health in adult life and other major causes of morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
1
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 24 publications
5
92
1
9
Order By: Relevance
“…We found no studies analysing the social pattern of tracking of low back pain, but authors argue that adolescents from low SEP are likely to have a higher prevalence of persistent low back pain into adulthood simply due to their higher risk of achieving jobs that are more physically demanding (C) [23]. Two longitudinal studies that were unable to detect socioeconomic differences in back pain in adolescence/early adulthood, showed that these socioeconomic patterns developed over time [21,24]. The socioeconomic patterning of back pain in adulthood was partly explained by lifestyle factors and adverse life events and by higher prevalence of poor working conditions, poor mental health, and psychological distress in low SEP, indicating socially differential vulnerability as part of the possible mechanism (D).…”
Section: Physical Healthmentioning
confidence: 84%
“…We found no studies analysing the social pattern of tracking of low back pain, but authors argue that adolescents from low SEP are likely to have a higher prevalence of persistent low back pain into adulthood simply due to their higher risk of achieving jobs that are more physically demanding (C) [23]. Two longitudinal studies that were unable to detect socioeconomic differences in back pain in adolescence/early adulthood, showed that these socioeconomic patterns developed over time [21,24]. The socioeconomic patterning of back pain in adulthood was partly explained by lifestyle factors and adverse life events and by higher prevalence of poor working conditions, poor mental health, and psychological distress in low SEP, indicating socially differential vulnerability as part of the possible mechanism (D).…”
Section: Physical Healthmentioning
confidence: 84%
“…Macfarlane et al found a relationship of pain with adult and childhood SES (although the latter was less strong), which was partly explained by adverse life events and psychological distress, but they did not examine educational variables [16]. Hagen et al examined an occupationally disabled back pain population and found a strong effect for education as a 'protective' factor, even after controlling for the 50% variance in pain attributable to occupational class, working conditions and lifestyle factors [9].…”
Section: What Factors Mediate An Association Between Cp and Ses?mentioning
confidence: 99%
“…Two cross-sectional studies explored mediation [9,16]. Macfarlane et al found a relationship of pain with adult and childhood SES (although the latter was less strong), which was partly explained by adverse life events and psychological distress, but they did not examine educational variables [16].…”
Section: What Factors Mediate An Association Between Cp and Ses?mentioning
confidence: 99%
“…A growing body of evidence suggests a link between psychological ill-health and the development and maintenance of fibromyalgia [1][2][3][4][5][6][7]. Psychological factors that have been shown to influence fibromyalgia include childhood abuse, traumatic life events, work stress, and socioeconomic status, among others.…”
Section: Introductionmentioning
confidence: 99%